Optimal Fractional‐Order Proportion Integration Differentiation Control of Proton Exchange Membrane Electrolyzer for Offshore Wind Power Hydrogen Production System - Tong, Fan; Wei, Wuqing; Jin, Mingyue; Sun, Xi; Wang, Qiuyuan; Luo, Qin (Energy technology (Weinheim, Germany), 2023)
Offshore wind power is mostly of strong randomness and unpredictability, which brings a great challenge to proton exchange membrane (PEM) water electrolysis‐based hydrogen production. Besides, volatile temperature and pressure tend to impose prominent impacts on electrolyzer parameters as well. By analyzing the electrochemical characteristics of PEM electrolyzers, the electrochemical model of PEM electrolyzer in offshore wind power generation hydrogen production system is established. To ensure the control performance of PEM electrolyzers, the fractional‐order proportion integration differentiation (FOPID) control strategy and the improved firefly algorithm (IFA) are introduced, and the relevant parameters are optimized according to the overshoot and stability time as evaluation indicators. In order to adapt to the FOPID control requirements, a step‐type inertia weighting factor is employed to improve the classical firefly algorithm to avoid local optimum, and a mutation mechanism is used to expand the search range. Verification results show that the proposed IFAFOPID controller is superior to the traditional PID controller with a smaller overshoot and a shorter transition time subject to different disturbances, and thus is more beneficial to achieve precise voltage control and obtain stable hydrogen output. Herein, the electrochemical model of proton exchange membrane electrolyzer in offshore wind power generation hydrogen production system is established, and the fractional‐order proportion integration differentiation (PID) control strategy and the improved firefly algorithm are introduced to ensure the control performance. Verification results show that the proposed control method is superior to the traditional PID control method.